Rapid-acting insulin glulisine: an update on clinical experience. Issue 4 (July 2011) - Dailey, George
This comprehensive article on insulin glulisine (glulisine; Apidra ®®, sanofi-aventis [Paris, France]) is an update to a previous review from 2006. Glulisine is a rapid-acting insulin analog that mimics physiologic postprandial insulin secretion more closely than regular human insulin and other insulin analogs. Glulisine can be taken pre- or post-meal, providing patients with more flexibility regarding meal content and timing. In patients with Type 2 diabetes, multiple trials, including observational studies, have demonstrated that glulisine (combined with insulin glargine or oral antidiabetic drugs) is superior to regular human insulin in terms of glycemic control, patient satisfaction and quality of life. When utilized in accordance with recommended use, patients can safely intensify from basal insulin to basal insulin plus a single prandial dose, through to a basal––bolus regimen without loss of efficacy and without a significantly increased risk of hypoglycemia. Glulisine is safe when used in insulin pump therapy and provides an effective and versatile tool for postprandial glycemic control.